2018
DOI: 10.1371/journal.pone.0193535
|View full text |Cite
|
Sign up to set email alerts
|

Effects of truck-mounted, ultra low volume mosquito adulticides on honey bees (Apis mellifera) in a suburban field setting

Abstract: Few studies have examined the impact of mosquito adulticides on honey bees under conditions that reflect actual field exposure. Whereas several studies have evaluated the toxicity of mosquito control products on honey bees, most have been laboratory based and have focused solely on acute mortality as a measure of impact. The goal of this study was to determine effects of routine applications of truck-based ultra-low volume (ULV) mosquito adulticides (i.e., Scourge, Duet, and Deltagard) on honey bees in a subur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…Esterase levels reported in our study (Table 2) are low compared to those found by Carvalho et al (2013) demonstrated that organophosphorous insecticides and pyrethroids cause a reduction in activity in these enzymes; P 450 activity, on the other hand, seems to increase in the presence of organophosphorous compounds (Pokhrel et al, 2018;Yao et al, 2018). When comparing our results with those reported for mosquitoes, the concentrations we found are higher than in mosquitoes that have developed resistance to insecticides (8 x 10 − 3 pmol P 450 ) (Dzul et al, 2007).…”
Section: Discussioncontrasting
confidence: 50%
“…Esterase levels reported in our study (Table 2) are low compared to those found by Carvalho et al (2013) demonstrated that organophosphorous insecticides and pyrethroids cause a reduction in activity in these enzymes; P 450 activity, on the other hand, seems to increase in the presence of organophosphorous compounds (Pokhrel et al, 2018;Yao et al, 2018). When comparing our results with those reported for mosquitoes, the concentrations we found are higher than in mosquitoes that have developed resistance to insecticides (8 x 10 − 3 pmol P 450 ) (Dzul et al, 2007).…”
Section: Discussioncontrasting
confidence: 50%
“…This is problematic as successfully developing and implementing a mosquito control strategy goes hand in hand with possessing rigorous and accurate information on the likely distribution of a mosquito species, its host preferences, and when and where they are likely to be host seeking. These factors can vary greatly between mosquito species, or even within species, depending on their location and/or genetic background [ 58 , 59 ]. Without sufficient, high quality information on specific mosquito targets, developing persistent and effective control programs may prove challenging, particularly during outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrethrins have been used as competent pesticides with less well-known insecticide resistance traits in mosquitoes and other human pests while being safer in indoor domestic settings ( Cuervo-Parra et al 2016 , Smith et al 2016 ). Although considered an uncommon pest management technology, benefits to public health and future broader applications are undeniable as VOCs have proven to control insect vectors and reduce pathogen transmission while being a cost-effective alternative ( Giles et al 2011 , Pokhrel et al 2018 ). Incorporating VOCs into an IPM plan can reduce nontarget effects of classic pest control strategies, while providing enhanced suppression of pests through multiple modes of action.…”
Section: Team 3 Stance: the Use Of Volatile Organic Compounds Is The ...mentioning
confidence: 99%